PUISI-PUISI PERLAWANAN WIJI THUKUL DALAM PERSPEKTIF REALISME SOSIALIS GEORG LUKACS - Y.B. Agung Prasaja; Ambar Andayani (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2021)
In the collection of poems Aku ingin Jadi Peluru (2000), Wiji Thukul’s poems describe the social realities of poverty and repression which are suffered by proletarian people. His poems represent repression, cruelty of authority towards proletarian people. Thukul condition which is suffered in poverty and repression encourages him to protest unfairness bravely, to move social change, and to fight the cruelty of authority.